Gabriel Salazar Vergara Mercaderes, empresarios y capitalistas (Chile, siglo XIX) - Grez Toso, Sergio (Cuadernos de Historia, 2009)
Editorial Sudamericana, Santiago, 2009, 794 páginas, ISBN 978-956-262-330-8